Vulnerability assessment tools for historic facades - Fontenele, Amanda Daniel (2022)
Historic heritage can be classified as material, immaterial, natural, or immovable property with artistic, cultural, religious, documentary, or appealing meaning with importance for a particular society. While historic buildings are relevant to their societies, the lack of approaches, information, and techniques, with considering the particularities of this special group of structures makes emerging the necessity for advances in this area. Among the tools to support the management strategies of urban centers on what, when and how should be the intervention measures in heritage buildings is the vulnerability assessment. However, the assessment of the vulnerability of historic constructions requires the adoption of its own and appropriate methodology for a given purpose and scale of the analysis, requiring the identification of the main constructive aspects and existing damages. Among the elements that make up a building, the facade represents the architectural identity that exposes traces of the building patterns of an era. In addition, most of these buildings are owned by private individuals, making it difficult to access information. Thus, facades are the main means to obtain the constructive characteristics and evaluate the state of conservation of these buildings. Considering the extensive collection of historic buildings of the state of Ceará, the gap of the scientific information on the physical, mechanical characteristics, behavior and structural vulnerability highlights the necessity for the development of studies focused on these subjects. The present thesis aimed mainly at contributing to the evaluation, identification, and preservation of historic facades. For this, the research was divided into four complementary lines of investigation: (1) characterization of the historic centers of Ceará; (2) analysis and application of existing vulnerability assessment methods; (3) identification of the main damage to historic facades; and (4) creation of a qualitative methodology capable of assessing the vulnerability of historic facades through a vulnerability index called Vulnerability Index of Historic Facades (Vif).